The bald bandit - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 1997)
Third-grader Dink and his detective friends hope to receive a big reward by finding the person whose video recorder picked up a picture of the local bank robber.
"A Stepping Stone book."
"B"--Spine.
School Library Journal, January 1998
L.A. Recommended Foreign Language, February 1999
3.5
3-6
Keywords: Bank robberies -- Fiction; Mystery and detective stories; Bank robberies -- Fiction; Mystery fiction